Penerapan Budidaya Hidroponik Untuk Mengatasi Stunting dan Meningkatkan Asupan Gizi Masyarakat - Maulana, Deni; Basrol, Basrol; Nathasya, Wulan; Zuhra, Alfi; Barokah, Indah; Rostiana, Apriani; Nurismi, Nurismi (Medan Resource Center, 2024)
Stunting is still a serious public health problem in Indonesia with a prevalence of around 30.8%. This study aims to analyze the application of hydroponic cultivation as an effort to overcome stunting and increase community nutritional intake in Pulo Sarok Village, Singkil District, Aceh Singkil Regency. This research used a qualitative method with a participatory action research approach through the UTU Regular Community Service Program (KKN). Data collection was done through observation, interviews, and socialization to the community. The results showed that out of 133 households, 33 households (24.8%) were classified as poor with an average income of Rp1,000,000 - Rp3,000,000 per month. The stunting survey found 2 cases of suspected stunting, but after further examination did not meet the criteria for stunting diagnosis. The majority of the population work as farmers with abundant natural resource potential in the agricultural sector. The implemented hydroponic cultivation program has successfully provided an alternative source of nutritious food for the community and supported stunting prevention efforts through the provision of fresh vegetables that can be accessed sustainably.